Application of linked data technologies in digital libraries: a review of literature. Issue 3 (2nd May 2019) - Raza, Zahid; Mahmood, Khalid; Warraich, Nosheen Fatima
Abstract : Purpose: This paper aims to describe how linked data technologies can change the digital library collections, what are the benefits of linked data applications in digital libraries and what are the challenges of digital libraries in linked data environment. Design/methodology/approach: The present study is based on substantial literature review on the applications of linked data technologies in digital libraries. The search engines such as Google, Yahoo and Google Scholar were used to find the relevant literature for the study. Online databases such as Pro Quest, Science Direct, Emerald and JSTORE were also used to find the relevant literature of the study. Databases of Library Sciences Library and Information Science and Technology Abstracts and Library Information Science Abstracts were also used to find the relevant literature of the study. Library, linked data technologies, Semantic Web, digital library and digital collections were the main keywords which were used to find the relevant literature for the study. Findings: The evolution of linked data technologies and Semantic Web has changed the traditional role of the libraries. Traditional libraries are converting into digital libraries and digital libraries are in a struggle to publish their resources on the Web using XML-based metadata standards. It has made capable the digital collections to be viewed by machines on the Web just like human. On the emergence of linked data applications in digital libraries, Web visibility of the libraries has been enhanced to provide the opportunities for the users to find their required quality information of libraries round-the-clock on the Web. National Library of France, National Library of Spain, Europeana, Digital Public Library of Americana, Library of Congress and The British Library have taken the initiatives to publish their resources on the Web using linked data technologies. Originality/value: This study present several key issues for policy makers, software developers, decision makers and library administrators about linked data technologies and its implementations in digital libraries. The present study may play its role to facilitate the users of the Web who are enthusiastically interested to exploit the quality and authentic library resources on the Web round-the-clock. Search engines will also achieve their longstanding goal to exploit the quality resources of the libraries for their Web users to make their Web appearance more credible and trustworthy.